2014
DOI: 10.17294/2330-0698.1025
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Chemotherapy-Induced Cardiotoxicity

Abstract: Follow this and additional works at: https://aurora.org/jpcrr Part of the Cardiology Commons, and the Oncology CommonsJournal of Patient-Centered Research and Reviews ( JPCRR) is a peerreviewed scientific journal whose mission is to communicate clinical and bench research findings, with the goal of improving the quality of human health, the care of the individual patient, and the care of populations. Recommended CitationPizzino F, Vizzari G, Bomzer CA, Qamar R, Carerj S, Zito C, Khandheria BK. Diagnosis of che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 34 publications
0
11
0
1
Order By: Relevance
“…Type I, characteristic of anthracyclines, appears to be due to the direct oxidative stress-induced death of cardiomyocytes. It is an irreversible, dose-dependent and easily identifiable process at myocardial biopsy [22]. Conversely, type II corresponds to trastuzumab-induced cardiotoxicity, characterized by a transient deterioration of myocardial function without resulting in cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Type I, characteristic of anthracyclines, appears to be due to the direct oxidative stress-induced death of cardiomyocytes. It is an irreversible, dose-dependent and easily identifiable process at myocardial biopsy [22]. Conversely, type II corresponds to trastuzumab-induced cardiotoxicity, characterized by a transient deterioration of myocardial function without resulting in cell death.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study by Lisi et al (2014) showed that in breast cancer patients receiving anthracycline chemo-therapy, cardiac systolic and diastolic function have decreased immediately after the onset of chemotherapy. CHF may occur after cumulative dosage of doxorubicin 550 mg/m2 or more (Torres et al 2012, Pizzino et al 2014, Lisi et al 2014. Studies by Ismail mention that the emergence of cardiotoxic effects of doxorubicin, which is characterized by decreased LVEF, occurs in cumulative doses of >300 mg/m2.…”
Section: Discussionmentioning
confidence: 99%
“…Период субклинического поражения миокарда ЛЖ может не проявляться симптомами сердечной недостаточности и не выявляться стандартным методом эхокардиографии (ЭхоКГ). Одними из наиболее кардиотоксичных химиопрепаратов являются антрациклиновые антибиотики, вызывающие необратимое повреждение кардиомиоцитов с развитием апоптоза [3].…”
Section: ââåäåíèåunclassified